Pemanfaatan ChatGPT untuk Pengotimalan Copywriting pada Madaris Jakarta Islamic Center - Prasetyo, Johan Hendri; Sarasati, Fajar; Mazia, Lia; Astuti, Widi (Jurnal Abdimas Perbanas, 2024)
The existence of digital disruption and millennial disruption in Indonesia has an impact on competition in all industrial sectors, both commercial and non-commercial industries, including the Jakarta Islamic Center Islamic Youth and Youth Council (Madaris). With increasingly massive digital developments, Madaris JIC must be able to adapt to develop the economy for the organization and its members. The problem currently faced by Madaris JIC is the difficulties experienced by Madaris JIC in empowering and improving the economy of the organization and its members, especially with the lack of experience in marketing products and advertising messages that are less attractive. This is of course a problem that must be addressed immediately, one of which is by training on the use of ChatGPT to optimize copywriting among organizations and their members. Therefore, Lecturers and Students of the Digital Business Study Program held community service with the aim of helping Jakarta Islamic Center Mosque Youth in empowering the economy for the organization and its members